Comorbid neuropsychiatric and autonomic features in REM sleep behavior disorder. (2020) - Barone, Daniel A.; Wang, Fei; Ravdin, Lisa; Vo, Mary; Lee, Andrea; Sarva, Harini; Hellmers, Natalie; Krieger, Ana C.; Henchcliffe, Claire
Abstract: Objective: Our aim is to define the extent of comorbidities in order to improve clinical care of patients with idiopathic rapid eye movement sleep behavior disorder (iRBD) utilizing the REM Sleep Behavior Disorder Associations with Parkinson's Disease Study (RAPiDS) cohort. Methods: Consecutive adult study participants with iRBD confirmed on polysomnogram (PSG) were prospectively recruited from the Weill Cornell Center for Sleep Medicine. Evaluations comprised multiple facets of sleep, neurological, autonomic, and psychiatric function. Results: Participants evaluated included 30 individuals with iRBD, with mean 1.5 ± 2.3 years from PSG to neuropsychiatric evaluation. Mean age was 59.5 ± 16.0 years at time of PSG, and 6/30 were women. Urinary difficulties were reported in 14/30 (47%): slight 7 (23%), mild 4 (13%), moderate 2 (7%), and severe 1 (3.0%). Ten out of 29 (34%) had abnormal Montreal Cognitive Assessment (MoCA) scores and the mean was 26.5 ± 3.2. The distribution of MoCA scores was significantly associated with urinary problems insofar as the more severe urinary problems were, the lower the MoCA scores (p = 0.04). Conclusions: In this RAPiDS cohort, we detected an unexpectedly high occurrence of non-motor dysfunction. Our results point to the need for screening patients with iRBD for complaints that are actionable, for example those affecting mood, cognition, urinary function, and bowel function. We propose the term RBD+ to be used to identify such individuals. For the quality of life in patients diagnosed with RBD, a closer look by the clinician should be enacted, with appropriate referrals and workup. Highlights: Comorbidities in idiopathic rapid eye movement sleep behavior disorder (iRBD) is further defined. REM Sleep Behavior Disorder Associations with Parkinson's Disease Study (RAPiDS) cohort There was a high occurrence of non-motor dysfunction in this cohort. The need for screening patients with iRBD for complaints that are actionable was demonstrated. We proposed the term "RBD+" to be used to identify such individuals.